Kemampuan Kelompok Wanita Tani Sri Rejeki dalam Pengolahan Kripik Ketela di Desa Dawan Klod Kecamatan Dawan, Kabupaten Klungkung - PRATIWI, NI LUH GEDE MIRAH WISNU; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The ability of Women Farmer Group Sri Rejeki in Processing Chips Cassava in the village of Dawan Klod, Dawan Sub-district, Klungkung Regency The objectives of this research are: (1) To know the profile of Sri Rejeki farmer; (2) To know the ability of Women Farmer Group Sri Rejeki in Processing Chips Cassava. This research was conducted at Women Farmer Group Sri Rejeki businessman in Chips Cassava in Dawan Klod Village, Dawan Sub-district, Klungkung Regency taken deliberately. Qualitative and quantitative descriptive data analysis methods. The results showed that, (1) Women Farmer Group Sri Rejeki stood on October 22, 1998, a member of 10 people, chairman Ni Nyoman Simprig. Production capacity of cassava chips per day 1,500 pcs and in order to increase to 2,500 pcs or more; (2) The ability of Women Farmer Group Sri Rejeki in processing Chips Cassava including medium category with score 3,20. From the results of this study can be suggested: (1) Farmers group of women as Community Direct Assistance fund users need to improve the performance and quality of its processed products, so as to increase the selling value and income of groups and individuals; (2) Community Direct Assistance program for the domestic industry should be developed not only within the city but also in the countryside, thus it is expected that farmers' production can be absorbed as raw material for processed products.